Exploration of Theoretical and Antioxidant Mimetic Activities of Binuclear Copper(II) and Nickel(II) Coordination Complexes - Mohan, Bharti; Choudhary, Mukesh (Asian Journal of Chemistry, 2021)
Three dinuclear copper(II) and nickel(II) complexes viz. [Cu2(La)(py)2]·(ClO4)2 (1), [Ni2(Lb)(ImH)2]·(ClO4)2 (2) and [Ni2(Lc)(H2O)2]·(ClO4)2 (3) were designed and synthesized using disulfide and auxiliary ligands as functional models for antioxidant superoxide dismutase enzyme (where, H2La-H2Lc = disulfide ligands bearing S-S bond, py = pyridine, ImH = imidazole). The disulfide ligands were synthesized by condensation reaction of 2-(2-(2-aminophenyl)disulfanyl)benzeneamine with 3-bromo-2-hydroxy-5-nitrobenzaldehyde; 5-bromo-2-hydroxybenzaldehyde and 3,5-dichloro-2-hydroxybenzaldehyde, respectively. All the compounds were characterized by various spectrometry methods. The molecular docking study was performed against penicillin binding protein 4 (PBP4) active site pocket and E. coli DNA Gyrase B ATPase domain to evaluate the possible mechanism of antibacterial property of disulfide ligands. The results revealed that H2La-H2Lc possess higher binding affinity for active site of PBP4 and Gyrase B ATPase domain. The present study also demonstrated that disulfide compounds have potential to inhibit the PBP4 and Gyrase B ATPase domain and can be developed as lead compounds. In addition, antioxidant superoxide dismutase (SOD) activity is also discussed of these complexes. The antioxidant superoxide measurements show that complexes behave as superoxide mimic in alkaline nitro blue tetrazolium chloride (NBT) assay.